A novel strategy for fabricating highly stretchable and highly conductive photoluminescent ionogels via an in situ self-catalytic cross-linking reaction in ionic liquids. Issue 17 (19th April 2021) - Hao, Shuai; Zhang, Jianxin; Yang, Xuemeng; Li, Tianci; Song, Hongzan
Abstract : Novel luminescent ionogels with excellent stretchability, high ionic conductivity, and good temperature tolerance were fabricated via a self-catalytic cross-linking method. Abstract : We report a new method to fabricate highly stretchable and highly conductive fluorescent ionogels via self-catalytic cross-linking of poly(ionic liquid (IL))-based copolymers containing epoxy groups in ILs without adding any conventional cross-linkers and chromophores. Here, the ILs serve as a solvent, electrolyte, and catalyst, while the product of the ring-opening reactions acts as cross-linking junctions. The results reveal that these systems are typical autocatalytic systems and that the IL anion type significantly influences the curing reaction kinetics. These ionogels exhibit excellent stretchability (>1200%), high ionic conductivity (>1 mS cm −1 ), and good temperature tolerance (−40 to 200 °C). Surprisingly, the special cross-linking structures make the ionogels show typical aggregation-induced emission behavior and possess tunable photoluminescence properties. Moreover, ionogel-based strain sensors exhibit fast response speed, excellent temperature tolerance and stability, and can monitor various human motions. Therefore, our study provides a facile method to utilize several distinct properties of ILs and PILs for designing multifunctional ionogels that serve as flexible conductive and fluorescent materials.